An Original Testing Apparatus for Rapid Pull-Out Test - Aprialdi, D.; Lambert, S.; Jenck, O.; , Erizal; Widyarti, M. (Institute of Research and Community Outreach - Petra Christian University, 2014)
Pull-out test is commonly used to investigate the pull-out behavior of geotextile reinforcement embedded in soil. It is also used by different authors to propose interface friction angles values. Unfortunately these works mainly deal with cyclic loadings with reference to seismic action, which are believed to be different to the load exposed to reinforced earthworks due to lateral impacts. Therefore an original rapid pull-out test apparatus is proposed in this study. This article assess the proposed test method in addressing the rapid pull-out response of a geotextile embedded in soil. The testing apparatus allows investigating shear velocities within the range of 0.1 to 1.2 m/s. This test method seems promising in addressing the response of soil-geotextile interfaces under dynamic loadings. Nevertheless, improvements concerning the testing apparatus are still required. The loading system could be modified to avoid oscillations and specific equipment should be added to increase the normal stress.